Mickey é a vovozinha!: Níquel Náusea e a recepção dos quadrinhos no Brasil dos anos 1980 - Castelão, Erica Simões (2010)
This research is an analysis of Implicit Reader present in the work Níquel Náusea created by Fernando Gonsales for the purpose of understanding in which dimension the interaction between the author and public is configured in that narrative structure in the context of Brazil of the 1980s. The work was made based on theory of the structure of effect of the fictional text developed by Wolfgang Iser (1996). This theory was utilized observing the ideas produced by Eisner (1999; 2008) and McCloud (2005) about the graphical structure of comic books. It was done an analytical reading with the comic book entitled Níquel Náusea: este gibi é uma ratoeira (GONSALES, 1986, Ano I, nº 1), specifically the history named Níquel Náusea. The analysis was developed through the observations of the graphical elements – physical space, characters, subject of the verbal texts, the relation among the panels and the organization of narrative as a whole. Through of analysis of all that graphical elements the work aims to identify the ways that the texts has offered indications of sense that needs of the cooperation of the reader to come real during the process of reading.